Odpowiedź :
4.
[tex]a) 6x\\b)a+12\\c)\frac{x+y}{2} \\d) z-d\\e)(s^{3})^{2}[/tex]
5.
a) [tex]P=\frac{a*h}{2}= \frac{(3x-2)(5-x)}{2}=\frac{15x-3x^{2}-10+2x}{2}= \frac{-3x^{2}+17x-10 }{2}=-1,5x^{2}+8,5x-5[/tex]
b)[tex]P=\frac{a*h}{2} = \frac{(2a+b)(2b-a)}{2}=\frac{4ab-2a^{2}+2b^{2}-ab}{2}=\frac{-2a^{2}+2b^{2}-3ab}{2}=-a^{2}+b^{2}-1,5ab[/tex]
c)[tex]P=\frac{e*f}{2}= \frac{(3a-2)(6-2a)}{2}=\frac{18a-6a^{2}-12+4a }{2}=\frac{-6a^{2}+22a-12 }{2}= -3a^{2}+11a-6[/tex]
6.
a)[tex](3a+b)(b-2a)=3ab-6a^{2} +b^{2} -2ab= -6a^{2}+b^{2}+ab[/tex]
b)[tex](2a-3)(3-a)-(2+a)(2a-1)= 6a-2a^{2}-9+3a-(4a-2+2a^{2}-a)=6a-2a^{2}-9+3a-4a+2-2a^{2}+a= -4a^{2} +6a-7[/tex]
c)
[tex]2(a+3)(2a-5)-3(2-a)(2a+1)=2(2a^{2}-5a+6a-15)-3(4a+2-2a^{2}-a)=2(2a^{2}-11a-15)-3(-2a^{2}+3a+2)=4a^{2}-22a-30+6a^{2}-9a-6=10a^{2}-31a-36[/tex]
d)
[tex]-(3+2a)(a^{2}-3)= -(3a^{2}-9+2a^{3}-6a)=-(2a^{3}+3a^{2}-6a-9)=-2a^{3}-3a^{2}+6a+9[/tex]